Association between body mass index and blood pressure among adults - Thapa, Bindu; KC, Deepti; Shrestha, Kalpana; Gurung, Sunita (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Increase in body mass index increases risk of developing high blood pressure. Controversies have been found regarding the association of body mass index with high blood pressure. So, this study was conducted to find association between body mass index and blood pressure. Methods: A cross-sectional study was conducted among 245 adults of Pokhara, Lekhnath Metropolitan Ward No. 27 using convenient sampling method. The questionnaire was adopted from the step 2 (physical measurements) section of the WHO STEPS instrument. Results: Among 245 subjects, almost half (48.5%) of the subjects had normal body mass index. One-fourth (25%) of the subjects were overweight. About 60 percent of the respondents had normal systolic blood pressure. There were no significant positive correlations of body mass index with both systolic BP, diastolic BP and age. However, significant positive correlation was found between age and systolic BP. Conclusions: The study finding concluded that there are no significant positive correlations of body mass index with both systolic BP, diastolic BP and age. However, age and systolic BP has significant positive correlation. Therefore, with increase in age, regular monitoring of BP is required.